Endothelial Function in Postmenopausal Women: The Possible Role of Heat Shock Protein 60 and Serum Androgens - Armeni, Eleni; Soureti, Anastasia; Augoulea, Areti; Chondrou, Asimina; Drakoulis, Nikolaos; Kaparos, George; Delialis, Dimitrios; Stefos, Spyros; Angelidakis, Lasthenis; Sianis, Alexandros; Dimopoulou, Aggeliki-Maria; Alexandrou, Andreas; et al. (Frontiers in Molecular Medicine, 2022)
Background: Heat shock protein 60 (HSP60), a potentially homeostatic antigen, is involved in physiological and non-physiological conditions. Experimental data support the role of HSP60 in placental and mitochondrial steroidogenesis. Furthermore, HSP60 is translocated into the endothelial-cell plasma membrane and the extracellular space under stress conditions, promoting the atherosclerotic process. Therefore, we investigated the association between HSP60 and endothelial function in postmenopausal women, considering the possible atherogenic effect of androgenic hormones. Methods: This study included 123 healthy postmenopausal women. Exclusion criteria were treated hypertension or dyslipidaemia, menopause hormone therapy during the last 6 months, and previously diagnosed peripheral vascular disease or cardiovascular disease. Fasting venous blood samples were obtained for biochemical and hormonal assessment and evaluation of HSP60. Sonographic assessment of flow-mediated dilation (FMD) occurred immediately after that in one session. Results: Univariate analysis showed that women with FMD values below median 5.12% had lower logHSP60 values (low vs. high FMD, HSP60 values: 2.01 ± 1.16 ng/ml vs. 3.22 ± 1.17 ng/ml, p-value = 0.031). Multivariable analysis showed that logHSP60 was associated with FMD (b-coefficient = 0.171, p-value = 0.046), adjusting for traditional cardiovascular risk factors (TRFs) and insulin levels. Further adjustment for testosterone and DHEAS rendered the result non-significant. In the multivariable analysis, FMD was associated with insulin (b-coefficient = −0.166, p-value = 0.034), testosterone (b-coefficient = −0.165, p-value = 0.034), DHEAS (b-coefficient = −0.187, p-value = 0.017), adjusting for TRFs. Discussion: The results of this study indicate that the association between androgens and endothelial function is possibly mediated by HSP60 molecules, in women with low insulin resistance and androgenicity. Further prospective studies are needed to explore the significance of our findings.